Acute kidney injury during fasting in ramadhan in a patient with nephrolithiasis – a case report - Shalihin, Mohd Shaiful Ehsan; Mukhali, Hassan Basri (2018)
Fasting in Ramadhan is a religious obligation for every Muslim with its well-known good benefits for health.1 However, there is no specific guideline in terms of precaution for patients at risk to develop nephrolithiasis.  Nephrolithiasis and acute kidney injury may occur concomitantly due to its common risk factors which is dehydration. Poor oral intake due to inadequate preparation for fasting together with hot climate may contribute to the two related major problems.  Previous studies have highlight the recommendations for those having chronic kidney disease.1,2 However, studies on fasting complication in relation to acute renal impairment and nephrolithiasis are still insufficien